Characteristics of eco-friendly ultra-high-performance geopolymer concrete incorporating waste materials. Issue 14 (15th July 2022) - Tahwia, Ahmed M.; Abd Ellatief, Mohamed; Heneigel, Ashraf M.; Abd Elrahman, Mohamed
Abstract: Solid waste recycling is a cost-effective strategy to protect the environment, preserve natural resources, and minimize raw material usage. This study aims to assess the influence of waste materials (WM) on the performance of eco-friendly ultra-high-performance geopolymer concrete (UHPGC). A total of 10 specimens were incorporated with crushed glass (CG), ceramic (CC), and crumb rubber (CR). The flowability, setting time, and mechanical characteristics were experimentally determined. Besides, the microstructure and structural porosity development of waste materials-based UHPGC were investigated by using SEM and Mercury intrusion porosimetry (MIP). Furthermore, the relationship between the porosity and the mechanical characteristics was discussed. To generate the mixtures, WMs were used at three-volume dosages: 7.5%, 15%, and 22.5% as partial replacements of fine aggregate cured at ambient temperature. The findings were also compared to current standards and methodologies established in prior studies. The investigations revealed that the mechanical and microstructural characteristics of UHPGC descend significantly with the inclusion of 7.5% CC and CR, but are enhanced with increasing incorporation of CG. Importantly, the incorporation of CG into the produced UHPGC structure resulted in a greater reaction degree and a denser microstructure, which improved the results obtained from the mechanical properties and pore structure tests. As a result, the research showed that WM may be successfully used in UHPGC while still generating concrete with adequate properties for a variety of applications. Highlights: Fresh, mechanical and microstructure properties of UHPGC were investigated. The effect of incorporation of glass, ceramic, and rubber on the mechanical and microstructural properties of UHPGC. Accurate studies to define the microstructure performance of WM-based UHPGC.